Hospitalization prediction from the emergency department using computer vision AI with short patient video clips - Wui Ip; Maria Xenochristou; Elaine Sui; Elyse Ruan; Ryan Ribeira; Debadutta Dash; Malathi Srinivasan; Maja Artandi; Jesutofunmi A. Omiye; Nicholas Scoulios; Hayden L. Hofmann; Ali Mottaghi; et al. (npj Digital Medicine)
Abstract In this study, we investigate the performance of computer vision AI algorithms in predicting patient disposition from the emergency department (ED) using short video clips. Clinicians often use “eye-balling” or clinical gestalt to aid in triage, based on brief observations. We hypothesize that AI can similarly use patient appearance for disposition prediction. Data were collected from adult patients at an academic ED, with mobile phone videos capturing patients performing simple tasks. Our AI algorithm, using video alone, showed better performance in predicting hospital admissions (AUROC = 0.693 [95% CI 0.689, 0.696]) compared to models using triage clinical data (AUROC = 0.678 [95% CI 0.668, 0.687]). Combining video and triage data achieved the highest predictive performance (AUROC = 0.714 [95% CI 0.709, 0.719]). This study demonstrates the potential of video AI algorithms to support ED triage and alleviate healthcare capacity strains during periods of high demand.